The use of dietary supplementation among university students - Bińkowska-Bury, Monika; Więch, Paweł; Januszewicz, Paweł (Polish Journal of Public Health, 2010)
Introduction. The human diet is essential both for health and for well-being. The composition of the diet has to be diversified and adjusted to age, physical activity, occupation, and health. The diet should provide a proper supply of proteins, carbohydrates, fats, mineral components, and vitamins. Facing the dynamic development of the market of substitutes and complementary food and drink articles, special attention should be given to the scale of the use of dietary supplements among university students. Systematic monitoring of the scale of the dietary supplements use among university students would help to avoid abnormal behaviours in this respect, and influence the rational and safe use of dietary supplements. Aim. The aim of the study was to evaluate the prevalence of dietary supplements use among Rzeszów university students broken down by gender and field of study. Material and methods. The study included 208 students of the University of Rzeszów, studying the following majors: Polish, English, Russian and German philology, as well as physical education. In the statistical analysis, the chi-square test was used. Results. The majority of the students did not use dietary supplements (55.2%): herein the largest groups were men (70.5%) and physical education students (61.1%). Among those using dietary supplements, the most frequently bought preparations contained vitamins and mineral components (56.1%), as well as herbal extracts (15.7%). Gender (p=0.026) and the study field (p=0.023) affected the type of a frequently bought supplement. The students used dietary supplements according to recommendations included in the leaflet (88.0%) and did not need to consult the dietary supplements use with a doctor (41.1%). Conclusions. As a result of the study it was found that the majority of the students did not use any dietary supplements. Among those students who did not have contact with dietary supplements, men and physical education students prevailed. In the population of students using dietary supplements, the most frequently bought preparations contained: vitamins and mineral components, and herbal extracts. Gender and the study field had an influence on the type of the frequently bought supplements. Women preferred the following supplements: those affecting skin or nails, improving the immune system, intellectual processes, concentration, while men chose preparations improving the immune system and special supplements for sportsmen. The philology students often buy skin and nails-affecting supplements and those improving processes of thinking, concentration, as well as the immune system, and the physical education students - skin and nails-affecting supplements, preparations improving the immune system and special supplements for sportsmen. The students use dietary supplements according to recommendations included in the leaflet, and a large proportion of them (41.1%) did not need to consult the use of dietary supplements with a doctor.